The Role of Spiritual Well-being and Academic Resilience in Predicting Students’ Psychological Health - Mohammad Deymevar; Minoo Miri; Ali Tayarani Rad; Seyed Alireza Ghasemi (Health, Spirituality and Medical Ethics)
Background and Objectives: Studies have shown that spirituality and positive psychology constructs are effective factors in the psychological health of students. Accordingly, the current research was conducted to predict the psychological health of students based on the role of spiritual well-being and academic resilience. Methods: The present descriptive-correlational study was conducted on 353 students who were selected using a stratified sampling method. The data collection tools included the spiritual well-being questionnaire by Dehshiri et al., Goldberg’s psychological health questionnaire, and the academic resilience questionnaire by Samuels. SPSS software, version 26 was used for data analysis, employing the Pearson correlation test and multiple regressions. Results: The correlation between spiritual experiences and self-care behaviors with health anxiety was negative and significant (P<0.01). The components of spiritual well-being explained 37.1% and academic resilience 50.1% of the variance of psychological health. Conclusion: Spiritual well-being and academic resilience could predict students’ psychological health. Therefore, paying attention to the components of spiritual well-being and resilience should be considered by university administrators.